Handfuls of pasture for the beloved flock of Christ ; v.2 - MacKintosh, Charles Henry, 1820-1896 (London, UK G. Morrish)
Contents : Self -surrender ; "Accepted" and "Acceptable" ; A worshipper and a workman ; Christian life: what is it? ; The Christian priesthood ; The forsaken one ; The risen one - Jesus, a deliverer and lord ; The grace of God ; The God of peace ; The salvation of God ; God's way, and how to find it ; Landmarks and stumblingblocks
Brethren writer.
Keywords: Christian life